A survey among geriatricians on geriatric oncology and geriatric surgical oncology models in Europe - Paula Sobrini-Morillo; Isabelle Moens; Alfonso Cruz-Jentoft; Andrea Sebastiano Ciccone; Jugdeep K. Dhesi; Nicolas M. Gonzalez-Senac; Marije Hamaker; Cecilia Lund; Francesco Mattace-Raso; Nina Neuendorff; Siri Rostoft; David Shipway; et al. (European Geriatric Medicine, 2026)
Abstract Purpose To provide an up-to-date overview of geriatricians’ involvement in oncological and onco-surgical care for older adults across Europe. Methods An anonymous 35-item online survey was distributed via (inter)national societies between 10 April and 23 May 2025. The responses were summarized, and associations between comprehensive geriatric assessment (CGA) outputs, participation in oncological multidisciplinary team (MDT) meetings, and involvement in treatment decision-making were explored. Results A total of 2160 responses were received from 37 countries. Further analysis included 395 geriatrician/internal medicine respondents with > 25% survey completion from 34 countries. Of them, 19% reported no formal geriatric oncology model; the most common approaches were referral based on clinical judgment (43%) and a two-step pathway (42%). Frailty screening-guided referral occurred in 63%, with the G8 (50%) and Clinical Frailty Scale (32%) being the most commonly used. Among respondents, 30% reported routine MDT attendance, and 20% reported involvement in treatment decisions. In exploratory analyses, routine MDT participation was associated with active treatment decision-making (aOR 6.01, 95% CI 3.08–11.7), CGA-based recommendations addressing both geriatric domains and oncological treatment (aOR 5.81, 95% CI 3.16–10.7), and positive feedback from oncology/surgery teams (aOR 3.75, 95% CI 1.96–7.14; all p < 0.001). Only 39% of respondents were involved in inpatient surgical oncology care, with liaison models predominating (37%). Conclusion Geriatric oncology and geriatric surgical oncology remain unevenly implemented across Europe. Standardized pathways, training, and MDT integration may improve equity of care for older adults with cancer.